Exposure to toxic Alexandrium minutum activates the detoxifying and antioxidant systems in gills of the oyster Crassostrea gigas - Fabioux, Caroline; Sulistiyani, Yeni; Haberkorn, Hansy; Hegaret, Helene; Amzil, Zouher; Soudant, Philippe (Harmful Algae, 2015)
International audience Harmful algal blooms of Alexandrium spp. dinoflagellates regularly occur in French coastal waters contaminating shellfish. Studies have demonstrated that toxic Alexandrium spp. disrupt behavioural and physiological processes in marine filter-feeders, but molecular modifications triggered by phycotoxins are less well understood. This study analyzed the mRNA levels of 7 genes encoding antioxidant/detoxifying enzymes in gills of Pacific oysters (Crassostrea gigas) exposed to a cultured, toxic strain of A. minutum, a producer of paralytic shellfish toxins (PST) or fed Tisochrysis lutea (T. lutea, formerly Isochrysis sp., clone Tahitian (T. iso)), a non-toxic control diet, in four repeated experiments. Transcript levels of sigma-class glutathione S-transferase (GST), glutathione reductase (GR) and ferritin (Fer) were significantly higher in oysters exposed to A. minutum compared to oysters fed T. lutea. The detoxification pathway based upon glutathione (GSH)-conjugation of toxic compounds (phase II) is likely activated, and catalyzed by GST. This system appeared to be activated in gills probably for the detoxification of PST and/or extra-cellular compounds, produced by A. minutum. GST, GR and Fer can also contribute to antioxidant functions to prevent cellular damage from increased reactive oxygen species (ROS) originating either from A. minutum cells directly, from oyster hemocytes during immune response, or from other gill cells as by-products of detoxification.